Worker’s acceptance towards Malaysian Sustainable Palm Oil / Mohammad Zulkeflie Zakaria and Syahrizan Syahlan - Zakaria, Mohammad Zulkeflie; Syahlan, Syahrizan (Faculty of Plantation and Agrotechnology, 2018)
Acceptance towards something is really crucial especially those who involve in plantation industry. The implementation of Malaysian Sustainable Palm Oil (MSPO) will give a huge impact to company as well as the workers. Acceptance of workers towards MSPO should be noted as it can affect plantation operation and also the daily operation in estate. The objective of this study is to investigate the factors of workers acceptance towards MSPO and also to study the most dominant factor that will influence workers acceptance towards MSPO. A questionnaire was used to collect primary data about worker’s communication, training, estate support, attitude, knowledge and benefit towards their acceptance to MSPO. The surveys conducted at Syarikat Perladangan Peserta Kundang Sendirian Berhad (SPPK Sdn. Bhd.) There were 60 population of workers and only samples of 52 respondents were randomly selected based on Krejcie and Morgan table. Cronbach’s Alpha shows value more than 0.7 for all variables which indicates all the questions is consistent. Keiser-Meyer-Olkin (KMO) value is 0.690 near to 0.7 which means the sample is nearly adequate. The results show that the R Square is 0.770 which indicates 77% of workers acceptance being explained by the independent variables. Knowledge and communication have a strongly positive relationship while estate support has moderate positive relationship between acceptance. These correlation shows that these three factors are affecting the acceptance of workers. Result of regression shows that knowledge is the most dominant factor towards workers acceptance followed by communication and estate support. Hence, it can be concluded that all the objectives being answered.